Forage yield and morphogenesis of Brachiaria ruziziensis under nitrogen levels (Research, Society and Development, 2020)
With the objective to evaluate the effect of nitrogen levels (0, 60, 120, 180 and 240 kg of N ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics and nitrogen nutrition index (NNI) of Brachiaria ruziziensis, was carried out an experiment under field conditions in Roraima´s savannas. Nitrogen fertilization increased significantly (P